PENGARUH KORUPSI TERHADAP PEMBANGUNAN MANUSIA DI INDONESIA - Syahrul Hanafi (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The success of development is not sufficiently measured by using only economic measures but also must be supported by non-economic indicators. Where to measure the development of a State based on non-economic indicators that use Human Development Index (HDI). But in its activities, developing countries in both Asia and Africa are often hampered by high corruption practices. Based on this the authors are interested to see the effect of corruption on the provincial capitals in Indonesia. This study aims to see the effect of corruption in Indonesia as reflected in the Corruption Perception Index (IPK) on human development (HDI). The research design used is quantitative analysis. Sampling is done by using judgment sampling technique, where the research sample is some provincial capital in Indonesia with the data fulfill the criteria, so total data is 54 from 18 provincial capitals and three years of observation (2006, 2008, 2010). The analytical technique used to answer all objectives in this research is to use sregresi data panel analysis. The results show that simultaneously corruption adversely affects human development. This means that the higher the level of corruption, the lower the human development, where the effect of corruption on human development of 11.06%.